Pengaruh Good Corporate Governance dan Leverage Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023 - Fauzi Fajrul Falah; Elma Muktatiar Ramadani (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to analyze the influence of Good Corporate Governance (GCG) and leverage on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period. The main problems in this research include three important things: first, how to analyze managerial ownership of earnings management; second, what is the analysis of institutional ownership on earnings management; and third, how does GCG and leverage influence earnings management. The aim of this research is to examine the influence of managerial ownership on earnings management, examine the influence of institutional ownership on earnings management, and examine the influence of GCG and leverage on earnings management. The research method used is descriptive quantitative, with the research population consisting of the companies which are listed on the BEI. This research sample involves 99 companies with observations over three financial reporting periods from 2020 to 2023. The research results show that managerial ownership has a significant influence on earnings management, where the greater the managerial ownership, the lower the earnings management practices. Apart from that, institutional ownership also has a significant influence in reducing earnings management due to tighter supervision from institutional investors. Furthermore, implementing good GCG and proper leverage management has proven effective in reducing earnings management practices. This research confirms the importance of effective GCG implementation and wise leverage management in creating healthy and sustainable business practices.